Distribution and antifungal susceptibility of species causing vulvovaginal candidiasis and urinary tract infection in Medlatec healthcare system, Ha Noi city, Vietnam in 2023 - Pham Van Ngai; Tran Huu Dat; Luu Yen Nhi; Tran Thi Khanh Linh; Nguyen Thi Thu; Vu Lan Anh; Bui Thi Thu Dung; Pham Van Tran; Nguyen Thi Hien; Nguyen Thai Son; Trinh Thi Que; Do Ngoc Anh (Therapeutic Advances in Infectious Disease)
Background: Vulvovaginal candidiasis and urinary tract infections caused by Candida are common diseases. While the most common causative agent is C. albicans , other species, such as non- C. albicans , can also be responsible. Susceptibility to antifungal drugs varies among Candida species, but there is very limited information available from Vietnam. Objectives: To determine the species distribution and antifungal susceptibility patterns of Candida isolated from urine and vaginal samples of patients tested at the Medlatec healthcare system in 2023. Design: Cross-sectional study. Methods: The study describes a cross-sectional analysis of over 102 Candida isolates obtained from urine and vaginal samples of patients using the testing services at Vietnam Medlatec healthcare system from January to December 2023. Species identification of Candida isolates was performed using germ tube test and Vitek ® 2 systems. Antifungal susceptibility testing was carried out using the VITEK ® 2 card for yeast fungi. Minimum inhibitory concentrations for these isolates were classified according to the Clinical and Laboratory Standards Institute guidelines (M27-A3 and M27M44S-ED3). Results: In this investigation, five different Candida species were identified. Among these isolates, C. albicans (78.43%) was the most frequent, followed by C. tropicalis (11.76%), C. glabrata (4.91%), C. parapsilosis (1.96%), and C. krusei (0.98%). The resistance rates to fluconazole, voriconazole, caspofungin, micafungin, and amphotericin B were 7.7%, 4.2%, 4.0%, 1.0% and 1.0%, respectively. Conclusion: The most common species found in this population was C. albicans . Our findings also showed a high frequency of non- albicans Candida species causing fungal urinary tract infections. The resistance rates of isolated Candida strains to echinocandins and amphotericin B were low, while some strains were found to be resistant to fluconazole and voriconazole.